2012
DOI: 10.1111/febs.12068
|View full text |Cite
|
Sign up to set email alerts
|

The pseudophosphatase MKSTYX inhibits stress granule assembly independently of Ser149 phosphorylation of G3BP‐1

Abstract: The pseudophosphatase MK-STYX (mitogen-activated protein kinase phosphoserine/threonine/tyrosine-binding protein) has been implicated in the stress response pathway. The expression of MK-STYX inhibits the assembly of stress granules, which are cytoplasmic storage sites for mRNA that form as a protective mechanism against stressors such as heat shock, UV irradiation and hypoxia. Furthermore, MK-STYX interacts with a key component of stress granules: G3BP-1 (Ras-GTPase activating protein SH3 domain binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Mutations made in MK-STYX that restore this signature motif generate an active phosphatase (MK-STYX active ) [34] . Despite being catalytically inactive, MK-STYX plays a role in a number of important cellular pathways [34] [36] , including inhibition of apoptosis and stress granule formation [34] , [35] , [37] . The functionality of MK-STYX is underexplored and still remains elusive; however, as with active MKP homologs, determining its interaction partners has helped elucidate some of the functions of MK-STYX [34] , [38] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations made in MK-STYX that restore this signature motif generate an active phosphatase (MK-STYX active ) [34] . Despite being catalytically inactive, MK-STYX plays a role in a number of important cellular pathways [34] [36] , including inhibition of apoptosis and stress granule formation [34] , [35] , [37] . The functionality of MK-STYX is underexplored and still remains elusive; however, as with active MKP homologs, determining its interaction partners has helped elucidate some of the functions of MK-STYX [34] , [38] .…”
Section: Introductionmentioning
confidence: 99%
“…We determined that MK-STYX inhibits stress granule formation [34] . Dephosphorylation of G3BP-1 at Ser149 is critical for stress granule formation [39] ; however, MK-STYX's interaction with G3BP-1 and its effect on the stress granule pathway is independent of the phosphorylation status of Ser 149 [37] .…”
Section: Introductionmentioning
confidence: 99%
“…Hinton et al showed that overexpressed pseudo-phosphatase MK-STYX interacts with G3BP1 and inhibits the assembly of SGs, and first hypothesized that MK-STYX inhibition of SG assembly is G3BP-S149 dependent (Hinton et al, 2010), but subsequently showed that SG assembly is independent of S149 phosphorylation (Barr et al, 2013), using the original phosphomimetic (S149E) and non-phosphorylatable (S149A) mutants. Surprisingly, overexpression of mutationally-activated MK-STYX shows opposite effects; it induces rather than blocks SGs as does the native, enzymatically-dead version, and is capable of de-phosphorylating G3BP (Barr et al, 2013). Considering the SG-inhibitory effects of the S99P mutation in the S149E construct, it is possible that a clean S149E construct co-expressed with MK-STYX (native) would not have the same effects, as it allows the formation of SGs to the same extent as WT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report that there are additional mutations in the original pEGFP-C1-G3BP1-S149A and S149E constructs (Tourriere et al, 2003) that were generously shared and widely disseminated. These constructs were used in our study (Kedersha et al, 2016) and many other studies (Barr et al, 2013; Jedrusik-Bode et al, 2013; Kedersha et al, 2016; Kwon et al, 2007; Sahoo et al, 2018; Sahoo et al, 2012; Szaflarski et al, 2016). We have now identified second mutations within the NTF2-like domains of the original constructs.…”
Section: Introductionmentioning
confidence: 99%
“…This pseudophosphatase has the potential to affect different proteins/pathways, including ERKs (Reiterer et al, 2013), PTPMP1 (Niemi et al, 2014) and Ras signaling through interaction with G3BP‐1 (Barr et al, 2013). Downregulation of Styx caused an increase in 4E‐BP1 phosphorylation at T37/46, similarly to what was observed after APP depletion.…”
Section: Discussionmentioning
confidence: 99%